Pigtail chest drain-related organ injuries in preterm neonates - Bessalah, Laëtitia (International Journal of Contemporary Pediatrics, 2023)
Pigtail catheters are increasingly used in Neonatal Intensive Care Units. Despite being easier to position, presumably less invasive, and non-inferior to classic trocar drains, complications related to placement have been sporadically reported. We describe 3 cases of traumatic injury to neighboring organs and structures related to pigtail catheter positioning in small preterm infants. In the absence of formal neonatal guidelines, accurate estimation of needle and guidewire depth and ultrasonography guidance may contribute to prevent such dreadful complications.